Analisis Konsep Nusyuz dan Implikasinya dalam Perkara Perceraian di Pengadilan Agama Surabaya - Akbar Syahru Rama; Murni Murni (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
This research aims to analyze the concept and implications of nusyuz's actions in divorce cases in the Religious Courts. Nusyuz is defined as a wife's defiance of her obligations to her husband. Nusyuz is also often the basis for filing divorce lawsuits, especially divorce petitions for divorce by the husband. This study examines how nusyuz actions are taken into consideration by Religious Court judges in deciding divorce cases, as well as their impact on the wife's rights, such as those related to iddah liaving, mut'ah living, and child custody. By using normative juridical methods based on analysis of direct trials and court decisions, this research finds that nusyuz actions have significant legal consequences for wives, especially in terms of living and other rights after divorce. However, there are also variations in the judge's assessment of the evidence of nusyuz's actions, which has implications for the final outcome of the divorce case.